The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1104/pp.110.164095
|View full text |Cite
|
Sign up to set email alerts
|

FIBRILLIN4Is Required for Plastoglobule Development and Stress Resistance in Apple and Arabidopsis

Abstract: The fibrillins are a large family of chloroplast proteins that have been linked with stress tolerance and disease resistance. FIBRILLIN4 (FIB4) is found associated with the photosystem II light-harvesting complex, thylakoids, and plastoglobules, which are chloroplast compartments rich in lipophilic antioxidants. For this study, FIB4 expression was knocked down in apple (Malus 3 domestica) using RNA interference. Plastoglobule osmiophilicity was decreased in fib4 knockdown (fib4 KD) tree chloroplasts compared w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
79
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(85 citation statements)
references
References 76 publications
5
79
1
Order By: Relevance
“…FBN5 is a phylogenetically distant relative of other fibrillins in Arabidopsis (Singh and McNellis, 2011), and it localizes to the stroma, with a lower pI and lower hydrophobicity than the other fibrillins (Lundquist et al, 2012). Therefore, FBN5 may play different roles from those previously reported for the fibrillins that localize primarily to the plastoglobules (Trebst, 1978;Yang et al, 2006;Singh et al, 2010Singh et al, , 2012Youssef et al, 2010). Surprisingly, we found that FBN5 specifically interacts with two solanesyl diphosphate synthases, SPS1 and SPS2, in the chloroplasts.…”
Section: Introductioncontrasting
confidence: 48%
See 2 more Smart Citations
“…FBN5 is a phylogenetically distant relative of other fibrillins in Arabidopsis (Singh and McNellis, 2011), and it localizes to the stroma, with a lower pI and lower hydrophobicity than the other fibrillins (Lundquist et al, 2012). Therefore, FBN5 may play different roles from those previously reported for the fibrillins that localize primarily to the plastoglobules (Trebst, 1978;Yang et al, 2006;Singh et al, 2010Singh et al, , 2012Youssef et al, 2010). Surprisingly, we found that FBN5 specifically interacts with two solanesyl diphosphate synthases, SPS1 and SPS2, in the chloroplasts.…”
Section: Introductioncontrasting
confidence: 48%
“…It has been suggested that FBN4, with its lipocalin domain, is involved in the transport of PQ-9 and other molecules from the thylakoids to the plastoglobules (Singh et al, 2010(Singh et al, , 2012. However, the precise biological functions of the fibrillins require further investigation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both and Baldo et al (2010) noticed an induction of some photosynthetic genes during a Malus-E. amylovora interaction. Research by Singh et al (2010) suggested that FIBRILLIN4, which is associated with photosystem II, could also play a part in fire blight infections, as the disease is more expressed in the knockdown mutant.…”
Section: Photosynthesismentioning
confidence: 99%
“…Their shrinking and swelling in response to (a)biotic stresses and during developmental transitions, as well as in plastid biogenesis mutants, are well documented (Gaude et al, 2007;Simkin et al, 2007;Singh et al, 2010;Zhang et al, 2010). Recent results suggest that PGs are involved in active channeling of hydrophobic metabolites between the thylakoid and PG, permitted by the contiguous association of the two structures Gaude et al, 2007).…”
mentioning
confidence: 99%